ChemInform Abstract: A Rapid One‐Pot Five Component Sequential Access to Novel Imidazo[2, 1‐b]thiazinyl‐α‐aminophosphonates. Issue 30 (July 2016) - Kaur, Tanpreet; Saha, Debasmita; Singh, Neetu; Singh, Udai P.; Sharma, Anuj
Abstract: The two‐step sequential Groebke—Blackburn—Bienayme and Kabachnik—Fields reaction gives access to novel bisheterocyclic scaffolds through a microwave‐assisted one‐pot method.